Industrial policy in Europe since the Second World War: What has been learnt? - Geoffrey Owen (European Centre for International Political Economy (ECIPE), 2012)
Prompted by the revival of interest in industrial policy in several European countries, this paper considers what lessons can be learned from earlier European experience. The focus is mainly on sectoral or targeted industrial policy, designed to improve the performance of particular industries. Since the Second World War European industrial policy has passed through two phases. The first, starting in the 1960s, saw a series of attempts by governments, especially those of the UK and France, to create national champions in industries deemed essential to the health of the national economy. Among the favoured sectors were high-technology industries such as aerospace and computers; part of the motivation was to narrow the "technology gap" between Europe and the US. There was also a widely held belief in scale as the key to international competitiveness. With some exceptions these interventions were generally unsuccessful. Policy-makers tended to overrate the risks and costs of market failures and to underestimate those associated with government failures. There was also a mistaken assumption that there were certain technologies which a country somehow needed to have, and that they were more likely to be acquired through centralised direction than through competitive markets. The cost to the taxpayer of ill-judged industrial policy was high. (...)
Keywords: 330; Industriepolitik; Europa